Single-Cell Proteomics Analysis of Recurrent Low-Grade Serous Ovarian Carcinoma and Associated Brain Metastases - Pejovic, Tanja; Abate, Pierre-Valérien; Ma, Hongli; Thiessen, Jaclyn; Corless, Christopher L.; Peterson, Abigail; Allard-Chamard, Hugues; Labrie, Marilyne (Frontiers in Oncology, 2022)
Between 2-6% of epithelial ovarian cancer (EOC) patients develop brain metastases (brain mets), which are incurable and invariably result in death. This poor outcome is associated with a lack of established guidelines for the detection and treatment of brain mets in EOC patients. In this study, we characterize an unusual case of low-grade serous ovarian carcinoma (LGSOC) that metastasized to the brain. Using a spatial oriented single-cell proteomic platform, we compared sequential biopsies of a primary tumor with a peritoneal recurrence and brain mets. We identified several targetable oncogenic pathways and immunosuppressive mechanisms that are amplified in the brain mets and could be involved in the progression of EOC to the brain. More importantly, we were able to identify cell populations that are shared between the primary tumor and the brain mets, suggesting that cells that have a propensity for metastasis to the brain could be identified early during the course of disease. Taken together, our findings pave a path for personalized therapeutic decisions in LGSOC.